Religio-erotic Experience and Transoceanic Becoming at the Shoreline in Audre Lorde’s Zami - Coleman Taylor, Ashley (Journal of the American Academy of Religion, 2023)
Abstract In her biomythographical work Zami: A New Spelling of My Name, Audre Lorde’s lover Afrekete appears as a Black queer femme who alters her sense of self and her being through religio-erotic experience. After tracing the spirit who inspired Lorde’s Afrekete throughout the Americas, I propose a theory of the shoreline as a site of transoceanic becoming, or the experience of self-identification required to navigate the Western world as an African diaspora being. I focus primarily on the ontologies of Black trans and queer femmes and the unconscious yet necessary process of becoming at the intersections of existence.